2021
DOI: 10.1093/cercor/bhab162
|View full text |Cite
|
Sign up to set email alerts
|

Sex Chromosome Dosage Effects on White Matter Structure in the Human Brain

Abstract: Sex chromosome aneuploidies, a group of neurogenetic conditions characterized by aberrant sex chromosome dosage (SCD), are associated with increased risks for psychopathology as well as alterations in gray matter structure. However, we still lack a comprehensive understanding of potential SCD-associated changes in white matter structure, or knowledge of how these changes might relate to known alterations in gray matter anatomy. Thus, here, we use voxel-based morphometry on structural neuroimaging data to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Evidence for sex chromosome dosage effects on the human brain comes from observational research in groups with differing X and/or Y chromosome doses due to sex chromosome aneuploidy. Specifically, increasing X- and/or Y- chromosome dosage induces highly reproducible changes in diverse aspects of regional brain anatomy, including parieto-occipital cortical surface area (increased), lateral temporal cortical thickness (decreased), and volume of the cerebellum and globus pallidus (both decreased) [ 58 61 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for sex chromosome dosage effects on the human brain comes from observational research in groups with differing X and/or Y chromosome doses due to sex chromosome aneuploidy. Specifically, increasing X- and/or Y- chromosome dosage induces highly reproducible changes in diverse aspects of regional brain anatomy, including parieto-occipital cortical surface area (increased), lateral temporal cortical thickness (decreased), and volume of the cerebellum and globus pallidus (both decreased) [ 58 61 ].…”
Section: Main Textmentioning
confidence: 99%
“…Second, newer tools for brain-wide analyses of cell counts in mice show that many foci with sex-biased cellular compositions are also regions that show sex-biased volumes by sMRI [ 100 , 101 ]. Third, gonadal and sex chromosome factors that tend to differ between typical males and females have been shown to modulate sMRI measures of regional brain volume using experimental methods in mice [ 42 , 43 ] and observational data in humans [ 47 , 48 , 58 61 ].…”
Section: Main Textmentioning
confidence: 99%
“…This heightened influence of the X-chromosome-coupled with its comparatively lower total heritability to other tracts-complements existing knowledge about significant sex differences in the development of the corticospinal tract 50,51 . Further evidence suggests that increased X-chromosome dosage can notably decrease the white matter volume of the corticospinal tract 14 . This unique heritability of the corticospinal tract might stem from the additional dosage of X-escapee genes.…”
Section: Resultsmentioning
confidence: 99%
“…The X-chromosome is home to a wealth of genes predominantly expressed in brain tissues 10,13 as the chromosome-X to autosome expression ratio exceeds one 10 , underscoring the pronounced influence of the X-chromosome on brain anatomy, connection, and functions [14][15][16][17] . Mounting evidence has shown that the X-chromosome significantly impacts a myriad of neurological diseases and psychiatric disorders from both genetic and epigenetic viewpoints 5,[18][19][20] .…”
Section: Genetic Architecturementioning
confidence: 99%
See 1 more Smart Citation